Aetiologies of bacterial tick-borne febrile illnesses in humans in Africa: diagnostic limitations and the need for improvement - Adamu, Abdulrahman; Reyer, Flavia; Lawal, Nafiú; Hassan, Abdurrahman Jibril; Imam, Mustapha Umar; Bello, Muhammad Bashir; Kraiczy, Peter (Frontiers in Medicine, 2024)
Tick-borne febrile illnesses caused by pathogens like Anaplasma spp., Bartonella spp., Borrelia spp., Ehrlichia spp., Coxiella burnetii, Francisella tularensis, and Rickettsia spp., are significant health concerns in Africa. The epidemiological occurrence of these pathogens is closely linked to the habitats of their vectors, prevalent in rural and semi-urban areas where humans and livestock coexist. The overlapping clinical presentations, non-specific symptoms, and limited access to commercially available in vitro diagnostics in resource-limited settings exacerbate the complexity of accurate diagnoses. This review aimed to systematically extract and analyze existing literature on tick-borne febrile illnesses in Africa, highlighting the diagnostic challenges and presenting an up-to-date overview of the most relevant pathogens affecting human populations. A comprehensive literature search from January 1990 to June 2024 using databases like PubMed, Cochrane Library, Science Direct, EMBASE, and Google Scholar yielded 13,420 articles, of which 70 met the inclusion criteria. Anaplasma spp. were reported in Morocco, Egypt, and South Africa; Francisella spp. in Kenya and Ethiopia; Ehrlichia spp. in Cameroon; Bartonella spp. in Senegal, Namibia, South Africa, and Ethiopia; Borrelia spp. in Senegal, Gabon, Tanzania, and Ethiopia; Coxiella burnetii in 10 countries including Senegal, Mali, and South Africa; and Rickettsia spp. in 14 countries including Senegal, Algeria, and Uganda. Data were analyzed using a fixed-effect model in R version 4.0.1 and visualized on an African map using Tableau version 2022.2. This review highlights the urgent need for improved diagnostics to better manage and control tick-borne febrile illnesses in Africa.